Etiopathogenesis of dermatitis herpetiformis. - Rybak-d’Obyrn, Joanna; Placek, Waldemar (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2022)
Dermatitis herpetiformis is a rare chronic, autoimmune bullous disease linked to gluten sensitivity with intense pruritus and characteristic skin eruptions. Etiopathogenesis is complex and not fully understood. It is currently considered to be a specific cutaneous manifestation of celiac disease. Genetic, environmental and immunological factors influence both conditions. Exposure to gluten is the starting point of an inflammatory cascade leading to the formation of circulating IgA antibodies against tissue transglutaminase and skin immune IgA deposition followed by skin lesions. Binding of the immune complex deposits of IgA transglutaminases and epidermal antibodies with enzymes in the papillary dermis stimulates complement activation, neutrophil influx, proinflammatory cytokine release and overproduction of matrix metalloproteinases. We have collected current knowledge of the pathogenesis of dermatitis herpetiformis.